Pigment epithelium-derived factor (PEDF) negates hyperandrogenic PCOS features. Issue 2 (May 2020) - Miller, Irit; Bar-Joseph, Hadas; Nemerovsky, Luba; Ben-Ami, Ido; Shalgi, Ruth
Abstract : Polycystic ovary syndrome (PCOS), one of the most common female endocrine disorder, is a prevalent cause of infertility. Hyperandrogenism is a key feature in PCOS and is correlated with increased expression of VEGF and cytokines in the ovaries. We have previously shown that pigment epithelium-derived factor (PEDF), an endogenous protein, presents potent anti-angiogenic and anti-inflammatory activities in the ovary and negates the effects of cytokines and VEGF. Additionally, PEDF plays a role in both pathophysiology and treatment of ovarian-hyperstimulation syndrome (OHSS), frequently seen in PCOS patients. We established hyperandrogenic-PCOS models, both in vivo, using mice exposed prenatally to dihydrotestosterone (DHT) and, in vitro, using human primary granulosa cells (hpGCs) and human granulosa cell line (KGN). In PCOS-induced mice, the mRNA levels of I l-6, V egf and Amh were higher than those of control; yet, treatment with rPEDF decreased these levels. Moreover, treating OHSS-induced PCOS-mice with rPEDF alleviated all OHSS symptoms. Stimulation of hpGCs with DHT resulted in downregulation of PEDF mRNA expression, concomitantly with a significant increase in IL-6 and IL-8 mRNAs expression. However, co-stimulation of DHT with rPEDF attenuated the increase in cytokines expression. The anti-inflammatory effect of PEDF was found to be mediated via PPARγ pathway. Our findings suggest that rPEDF treatment may normalize the ovarian angiogenic-inflammatory imbalance, induced by PCOS-associated hyperandrogenism. Moreover, the therapeutic potency of PEDF in preventing OHSS symptomes offers a rationale for using PEDF as novel physiological treatment for PCOS sequels.